Legal analysis of final award of Court of Arbitration for Sport number CAS 2024/A/10310 about the FC Barcelona’s audiovisual rights - Hedi Dina Bangun Mentari; Tio Andharu Wikampha Narulita; Akmal Wiryawan Aditya Putra (Faculty of Law Universitas Negeri Surabaya, 2024)
Football Club Barcelona is a football club based in Barcelona, Spain, registered with the Royal Spanish Football Federation. FC Barcelona is currently appealing against a decision made by the Spanish National Competition Commission. In 2010, FC Barcelona entered into a contract with Mediaproductión SL, where Mediaproductión acquired the audiovisual rights for four seasons: 2010/11, 2011/12, 2012/13, and 2013/14. However, the General Law of Audiovisual Communication 7/2010 stipulates that the maximum duration for audiovisual rights agreements is three years, which contradicts the contract with Mediaproductión and violates a resolution issued by the CNC on 14th April 2010. FC Barcelona operates as a sports club (asociación civil in Spanish), a legal structure that restricts the club from receiving capital injections, which many other clubs use when facing financial difficulties. To address these difficulties and ensure the club's long-term sustainability, FC Barcelona chose to restore its equity by selling non-sports assets. The sale was classified by FC Barcelona as relevant income for UEFA's Financial Fair Play (FFP) break-even calculations. This classification was made after assessments by auditors, advisors, and experts, as well as consideration of LaLiga's FFP system, and relevant Spanish and EU law. The core issue in this case arises from FC Barcelona’s misclassification of its profits from the sale for the 2022/23 season's break-even submission. UEFA argues that FC Barcelona incorrectly classified the profits as other operating income instead of profit on the disposal of intangible assets, as per the applicable regulations. UEFA further claims that FC Barcelona deliberately deviated from its own financial statements and misled the authorities in its submission. UEFA, the governing body of European football, headquartered in Nyon, Switzerland, and recognized by FIFA, maintains that FC Barcelona's actions were in breach of Articles 58 (1) and (2) CL&FFP and Article 77.01 (e) L&FS, which are part of the financial regulations governing clubs' financial fair play and their break-even calculations. The dispute involves whether FC Barcelona misrepresented its financial situation in relation to its compliance with UEFA FFP regulations and whether the classification of the sale profits as